2008
DOI: 10.1111/j.1743-6109.2008.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Adult Male Circumcision: Effects on Sexual Function and Sexual Satisfaction in Kisumu, Kenya

Abstract: Corresponding Author:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 54 publications
3
149
1
3
Order By: Relevance
“…In the Kenyan study (which had a nearly identical design and similar results), 64% of circumcised men reported much greater penile sensitivity postcircumcision. 127 At the 2-year followup, 55% of circumcised men reported having an easier time reaching orgasm than they had precircumcision, although the findings did not reach statistical significance. The studies' limitation is that the outcomes of interest were subjective, self-reported measures rather than objective measures.…”
Section: Sexual Satisfaction and Sensitivitymentioning
confidence: 66%
See 1 more Smart Citation
“…In the Kenyan study (which had a nearly identical design and similar results), 64% of circumcised men reported much greater penile sensitivity postcircumcision. 127 At the 2-year followup, 55% of circumcised men reported having an easier time reaching orgasm than they had precircumcision, although the findings did not reach statistical significance. The studies' limitation is that the outcomes of interest were subjective, self-reported measures rather than objective measures.…”
Section: Sexual Satisfaction and Sensitivitymentioning
confidence: 66%
“…126,127 Among 5000 Ugandan participants, circumcised men reported significantly less pain on intercourse than uncircumcised men. 126 At 2 years' postcircumcision, sexual satisfaction had increased significantly from baseline measures in the control group (from 98% at baseline to 99.9%); satisfaction levels remained stable among the circumcised men (98.5% at baseline, 98.4% 2 years after the procedure).…”
Section: Sexual Satisfaction and Sensitivitymentioning
confidence: 99%
“…12,13,28 The relatively short, post-circumcision follow-up period may not accurately reflect sexual function at a later time, resulting in risk of bias for this meta-analysis. 26,28,29 Furthermore, the study validity may be affected by several factors, including subjective selfreporting, lack of physiological or laboratory indicators of sexual dysfunction or consensus on what constitutes sexual dysfunction for individuals with different education levels, cultures and religions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Circumcision is generally considered as a simple, rapid operation with efficacy for protection against HIV and other sexually transmitted infections, as confirmed in numerous, highquality studies. [2][3][4][5][6][7] Circumcision has been reported to adversely affect sexual function; 8 however, the majority of studies, including highquality ones [9][10][11] and ones with data arising from randomized controlled trials (RCTs), 12,13 show no difference or improvement in sexual function, sensitivity and satisfaction after circumcision. All of the data were considered by the American Academy of Pediatrics in formulating its 2012 policy, which concluded that there were no adverse effects on these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the disagreement in urologic literature, informing patients regarding these potential effects may be warranted. [31][32][33][34] Although penile carcinoma is rare, its effects are devastating. Therefore, it is imperative to send adult foreskin for pathologic examination.…”
Section: Circumcisionmentioning
confidence: 99%